TEORI â€œINNEFABILITASâ€ MENURUT ALLAMAH THABATABAâ€™I - Fazeli, Seyyed Ahmad; Nur, Muhammad (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
This essay will attempt to explain some of the theories of inneff ability of Allamah h abatabaâ€™i, as in an earlier work we have explained the same concept as viewed by both W. Stace and William James. Some of the issues will be outlined in this article, that is whether the absolute can be expressed? If wahdÄh al-wujÅ«d (unity of being) asserts absoluteness, does this mean that there is no language that can describe it ? Then what exactly is the meaning of innefability? What does it mean that the experience of wahdÄh al-wujÅ«d can not be conceptualized, nor can it be described, nor can it be logical? If so, where then do words such as innefability, paradox and â€˜absoluteâ€™ originate from? What does it mean that this is unattainable by reason? h is work will reveal that the experience of the absolutely wahdÄh al-wujÅ«d can be expressed generally not in detail, by means that diff ers from peripatetic logic.